2002
DOI: 10.21273/hortsci.37.6.890
|View full text |Cite
|
Sign up to set email alerts
|

The Vegetative Response of 'Concord' Grapevines to Soil pH

Abstract: One- and 2-year-old 'Concord' (Vitis labruscana L.) grapevines were used to study the effect of soil pH on vegetative growth and nutrition. Ninety-eight, own-rooted, 'Concord' grapevines were planted in 94.6-L pots containing vineyard soil adjusted to seven soil pH levels ranging from 3.5 to 7.5. After the first growing season, seven vines from each soil pH treatment were randomly selected, destructively harvested, and measured for root and shoot growth. The remaining 49 vine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…obser.). Schindelbeck and Riha (1988) and Kidd and Proctor (2001) have found that decrease in soil pH caused an increased biomass allocation to roots; Bates et al (2002) found that when the soil pH was lower than 4.4 the root, shoot ratio increased in Vitis labruscana L. plants.…”
Section: Discussionmentioning
confidence: 99%
“…obser.). Schindelbeck and Riha (1988) and Kidd and Proctor (2001) have found that decrease in soil pH caused an increased biomass allocation to roots; Bates et al (2002) found that when the soil pH was lower than 4.4 the root, shoot ratio increased in Vitis labruscana L. plants.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the reduction of Cu availability and the increase of Ca and Mg in the soil, liming also increased the soil pH from 4.4 to 5.4 or 6.1, and it may have provided additional benefits to the young vines, such as by reducing the absorption of Al, which is toxic to plants, and by increasing the availability of phosphorus (P) to and the uptake of P by the roots, favoring growth (Bates et al, 2002). Increases of P within the plant increase the plant's nutritional status and also have an effect on Cu toxicity because within the roots, P binds to Cu and forms an insoluble complex, thus preventing interactions between Cu and the root cells, especially vascular tissue cells, and alterations to the root structure (Ferreira et al, 2014).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…2010] and other deciduous fruit trees [Kassa 2015]. Studies revealed that root and shoot developments of grapevines are negatively affected above a soil pH of 7.0 [Winkler et al 1974, Bates et al 2002. Vineyard soils with a pH greater than 7.5 typically cause nutrient imbalances in grapevines [Bates and Wolf 2008].…”
Section: Discussionmentioning
confidence: 99%
“…Around the world, grapevine is generally cultivated in regions where alkaline soils with low iron availability prevail. High bicarbonate solution in alkaline soils is the main cause of limeinduced chlorosis with its well-investigated negative effects on both yield and quality of grapes [Bates et al 2002]. Several agents have been examined for their biostimulant or biofertilizer potential to promote plant growth under stress conditions [Nadeem et al 2007, Karlidag et al 2011, Dilek and Sabir 2016.…”
Section: Introductionmentioning
confidence: 99%